Pengaruh Implementasi Model Project Based Learning (PJBL) Terhadap Motivasi dan Hasil Belajar Siswa di SMK Negeri 5 Sidrap - Sakwati Abidin; Purnamawati; Abdul Muis Mappalotteng (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This research is a quasi experimental research with one group pretest posttest design. One Group Pretest-Posttest Design is a research activity that provides an initial test (pretest) before being given treatment, after being given treatment then giving a final test (posttest). Data analysis techniques use descriptive analysis and paired sample T test hypothesis test analysis. The results of the study with descriptive analysis showed that there was an increase in student motivation and learning outcomes from "Good Enough" to "Good". Based on inferential analysis of motivation and learning outcomes, a Sig (2-tailed) value of 0.000 is obtained, which means that it is smaller than 0.05, indicating that there is an influence of Project Based Learning Model Implementation (pjbl) on student motivation and learning outcomes. Based on the data from the study, it can be concluded that the implementation of the Project Based Learning (pjbl) Model has an effect in increasing student motivation and learning outcomes.